Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1111/liv.13264
|View full text |Cite
|
Sign up to set email alerts
|

High serum lipopolysaccharide binding protein is associated with increased mortality in patients with decompensated cirrhosis

Abstract: Serum and AF LBP concentrations showed a high negative-predictive-value to exclude infection and SBP, respectively. High serum LBP was detected in patients without infection at presentation who died during the 90-day-follow-up period. Elevated serum LBP is a marker of short-term mortality in patients without overt bacterial infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 29 publications
1
14
0
4
Order By: Relevance
“…22 Thus, recent studies have focused on the LPS-binding protein (LBP) as a surrogate of BT and as a prognostic factor in cirrhosis. 23,24 LBP peaks in plasma 2-3 days after BT and may remain increased up to 3 days later. 25 Moreover, we hypothesize that the synthesis of LBP by hepatocytes may be altered in patients with liver insufficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Thus, recent studies have focused on the LPS-binding protein (LBP) as a surrogate of BT and as a prognostic factor in cirrhosis. 23,24 LBP peaks in plasma 2-3 days after BT and may remain increased up to 3 days later. 25 Moreover, we hypothesize that the synthesis of LBP by hepatocytes may be altered in patients with liver insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…This heterogeneity may be primarily due to technical difficulties in the quantification of circulating levels of LPS . Thus, recent studies have focused on the LPS‐binding protein (LBP) as a surrogate of BT and as a prognostic factor in cirrhosis . LBP peaks in plasma 2‐3 days after BT and may remain increased up to 3 days later .…”
Section: Discussionmentioning
confidence: 99%
“…LBP is a predictor of LC prognosis. e authors of [91] detected LBP levels in 88 patients with decompensated cirrhosis including 18 patients with infection and the others without infection and found that, in noninfective patients, those with lower level of LBP had a lower 90-day mortality than the high level (48.0% vs. 24.4%), and only high LBP (HR: 8.1) and MELD (HR: 1.1) were predictors of mortality in multivariate analysis, but this association was not observed in infective patients. In 58 critically ill cirrhotic patients with severe sepsis, Chen et al [92] found that the cumulative survival rate at 28 days was higher in the high serum LBP group (>46 ng/mL) than that in the low serum LBP group (<46 ng/mL) (72.7% vs. 16.7%), with the AUROC of 0.809, sensitivity of 72.7%, and specificity of 83.3%.…”
Section: Predicting the Infection Lc Patients Are Frequently Complicmentioning
confidence: 99%
“…We appreciate the comments on our manuscript by Yan-Yan Xuan and colleagues, 1 as well as the opportunity to respond to them.…”
Section: Response To Lipopolysaccharide Binding Protein Predicts Decomentioning
confidence: 94%
“…Thirdly, the aetiology of cirrhosis was already shown in our article. 1 The 48.9% was alcoholic, 27.3% viral, 15.9% non-alcoholicsteatohepatitis, 5.7% autoimmune disease, 1.1% cryptogenic and 1.1% Wilson's disease. The aetiology did not differ between patients with and those without infection.…”
Section: Response To Lipopolysaccharide Binding Protein Predicts Decomentioning
confidence: 99%